2012
DOI: 10.1152/ajpheart.00568.2012
|View full text |Cite
|
Sign up to set email alerts
|

A differing role of oxidative stress in the regulation of central and peripheral hemodynamics during exercise in heart failure

Abstract: This study sought to characterize the role of free radicals in regulating central and peripheral hemodynamics at rest and during exercise in patients with heart failure (HF). We examined cardiovascular responses to dynamic handgrip exercise (4, 8, and 12 kg at 1 Hz) following consumption of either a placebo or acute oral antioxidant cocktail (AOC) consisting of vitamin C, E, and α-lipoic acid in a balanced, crossover design. Central and peripheral hemodynamics, mean arterial pressure, cardiac index, systemic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
2
14
2
1
Order By: Relevance
“…Considering that PLM specifically isolates the group III mechanoreceptors, thought to be sensitized in HF, the similar MAP response to the initiation of continuous PLM, was somewhat surprising. However, this finding actually further supports previous work by Middlekauf et al [25] and our own group [26] that was unable to reveal any evidence of an exaggerated exercise pressor reflex during passive arm exercise and active handgrip exercise, respectively, in patients with HFrEF. It is acknowledged that the lower baseline MAP and the lack of an exaggerated exercise pressor reflex could be attributed to the patient's pharmacological therapies, but this approach was chosen to minimize risk and study these patients with their disease pharmacologically controlled.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that PLM specifically isolates the group III mechanoreceptors, thought to be sensitized in HF, the similar MAP response to the initiation of continuous PLM, was somewhat surprising. However, this finding actually further supports previous work by Middlekauf et al [25] and our own group [26] that was unable to reveal any evidence of an exaggerated exercise pressor reflex during passive arm exercise and active handgrip exercise, respectively, in patients with HFrEF. It is acknowledged that the lower baseline MAP and the lack of an exaggerated exercise pressor reflex could be attributed to the patient's pharmacological therapies, but this approach was chosen to minimize risk and study these patients with their disease pharmacologically controlled.…”
Section: Discussionsupporting
confidence: 92%
“…During exercise, patients with HF often exhibit reduced muscle blood flow and convective O 2 transport (3,10,27,38), as well as exaggerated renal vasoconstriction (19), implicating exaggerated total peripheral resistance (TPR) as a contributor to the EPR in HF (39). Recent work performed by our group, revealed that during knee extensor exercise patients with HF exhibit reduced femoral blood flow (3), which following partial blockade of lower limb muscle afferents was somewhat restored to the level of controls.…”
Section: Discussionmentioning
confidence: 99%
“…Following AO consumption, we documented a marked increase in circulating AO capacity, but the consequence of this intervention on vascular function was less clear, as administration of the AO did not alter the FMD or reactive hyperemia (RH, an index of microvascular function) responses compared with placebo in the HFrEF patients. This was followed up by a study employing HG exercise to more broadly examine the impact of oral AO consumption on arterial blood pressure and indices of both central (i.e., CO and systemic vascular resistance [SVR]) and peripheral (arm blood flow and vascular resistance) hemodynamics in HFrEF patients and age-matched controls [71]. Although AO ingestion significantly increased plasma ascorbate concentration and endogenous AO activity (catalase) in both the patients and controls, only in the patients with HF did this intervention result in a significant hemodynamic response.…”
Section: The Impact Of Oxidative Stress On Vascular Function In Agingmentioning
confidence: 99%
“…However, this did not appear to be the result of limb or skeletal muscle-specific changes in PVR. Together, these studies [47, 71] have identified a somewhat varied response to AO consumption in HFrEF, which likely reflects the complex and heterogeneous manner in which oxidative stress may impact the circulatory system in this patient group. Whether this AO intervention could prove efficacious in rescuing the decrement in vascular function identified using the PLM model has not been examined, but is certainly a worthy of future investigation.…”
Section: The Impact Of Oxidative Stress On Vascular Function In Agingmentioning
confidence: 99%